Persistent Peripheral Nervous System Damage in Simian Immunodeficiency Virus–Infected Macaques Receiving Antiretroviral Therapy. Issue 11 (November 2015) - Dorsey, Jamie L.; Mangus, Lisa M.; Hauer, Peter; Ebenezer, Gigi J.; Queen, Suzanne E.; Laast, Victoria A.; Adams, Robert J.; Mankowski, Joseph L.
Abstract : Abstract: Human immunodeficiency virus (HIV)–induced peripheral neuropathy is the most common neurologic complication associated with HIV infection. In addition to virus-mediated injury of the peripheral nervous system (PNS), treatment of HIV infection with combination antiretroviral therapy (cART) may induce toxic neuropathy as a side effect. Antiretroviral toxic neuropathy is clinically indistinguishable from the sensory neuropathy induced by HIV; in some patients, these 2 processes are likely superimposed. To study these intercurrent PNS disease processes, we first established a simian immunodeficiency virus (SIV)/pigtailed macaque model in which more than 90% of animals developed PNS changes closely resembling those seen in HIV-infected individuals with distal sensory neuropathy. To determine whether cART alters the progression of SIV-induced PNS damage, dorsal root ganglia and epidermal nerve fibers were evaluated in SIV-infected macaques after long-term suppressive cART. Although cART effectively suppressed SIV replication and reduced macrophage activation in the dorsal root ganglia, PGP 9.5 immunostaining and measurements of epidermal nerve fibers in the plantar surface of the feet of treated SIV-infected macaques clearly showed that cART did not normalize epidermal nerve fiber density. These findings illustrate that significant PNS damage persists in SIV-infected macaques on suppressive cART.